Dancing Jacobins : A Venezuelan Genealogy of Latin American Populism - Sánchez, Rafael, 1950- (Book collections on Project MUSE., 2016)
"Dancing Jacobins traces the populist 'monumental governmentality' that began to take shape in Venezuela and other Latin American nations around the time of independence, in response to the insistent return of subaltern populations in the form of crowds. Informed by a Bolivarian political theology, the nation's representatives, or 'dancing Jacobins, ' draw on the repertoire of busts, portraits, and equestrian statues of national heroes scattered across Venezuela in a montage of monuments and dancing--or universal and particular. To this day, the nervous oscillation between crowds and peoplehood intrinsic to this form of government has inflected the republic's institutions and constructs, which are haunted and imbued from within by the crowds they otherwise set out to mold, enframe, and address"--